Red meat intake as a suspicious factor of colorectal cancer at Sanglah General Hospital in 2017 - Ganeshwary Nishal Ganasan; Made Agus Dwianthara Sueta; Made Suka Adnyana (Intisari Sains Medis, 2019)
Background: Colon and rectal cancer (colorectal cancer) is cancer with high morbidity and mortality. Colorectal cancer is the second leading cause of death among men and women. This cancer is also the third most common malignant neoplasm in the world, and its incidence has increased in recent years. A high diet of red meat is one of the risk factors that can increase the likelihood of colorectal cancer.Aim: The study aims to determine the relationship between red meat consumption on the incidence of colorectal cancer.Method: This study is an unmatched paired case-control study conducted in Sanglah Hospital using patient medical record data from 2016 to 2017. The number of colorectal cancer group and control group samples are 52 people, each group. Samples were then interviewed on the red meat diet using the questionnaire guidelines. Data on the diagnosis of colorectal cancer was obtained through the patient's medical record at Digestive Surgery Polyclinic, Sanglah Hospital, Denpasar.Result: About 76.9% of colorectal cancer patients consume a high intake of red meat. Patients with colorectal cancer have a history of higher red meat intake than patients without colorectal cancer (OR = 9.048; 95% CI 3.716-22.026; p<0.001).Conclusion: Red meat intake is a significant factor in the incidence of colorectal cancer in Sanglah Hospital. Limiting the consumption of red meat is recommended to reduce the risk of colorectal cancer.